Confirmatory Evaluation of the Modified Medical Research Council Questionnaire for Assessment of Dyspnea in Patients with Chronic Obstructive Pulmonary Disease in Portugal - Ribeiro, Soraia (2022)
The Modified British Medical Research Council Questionnaire is considered an adequate and simple measure of breathlessness in chronic obstructive pulmonary disease. It is widely used in clinical practice in Portugal, but it still lacks confirmatory evaluation for the Portuguese setting. The aim of this study was to perform a cultural adaptation and validation of the Modified British Medical Research Council Questionnaire so that its most suitable version can be made available to researchers and clinicians in Portugal. Material and Methods: We performed a cross-sectional descriptive study involving patients with chronic obstructive pulmonary disease aged 40 years or older. We applied the Modified British Medical Research Council Questionnaire and the previously validated Portuguese-language version of the clinical questionnaire for chronic obstructive pulmonary disease between January and June 2019. We determined the agreement between the two questionnaires with kappa agreement, with a 95% confidence interval, and we used Spearman correlation to find a correlation between two scores. Results: The study included 65 patients managed in a hospital pulmonology clinic (aged 68 ± 7 years; with predicted FEV1 of 49.86% ± 16.5%). The Modified British Medical Research Council scale correlated significantly with all the domains and the overall score of the clinical questionnaire for chronic obstructive pulmonary disease (0.46 < r < 0.68; p < 0.001). In bilingual patients, interclass correlation coefficient was 0.912 (p < 0.001). Conclusion: The Portuguese version of the Modified British Medical Research Council Questionnaire is a valid instrument for measurement of breathlessness in chronic obstructive pulmonary disease.